Influence of saccharomyces uvarum on volatile acidity, aromatic and sensory profile of Malvasia delle Lipari wine - Muratore, Giuseppe (Array, 2007)
The present study investigated chemical and sensory properties of Malvasia delle Lipari DOC (Denomination of Controlled Origin) wine fermented with a cryotolerant strain of Saccharomyces uvarum, characterized by low levels of acetic acid production. In particular, experimental wine was tested for volatile acidity and for aromatic profile by gas chromatography and the results were compared with the same wine produced with a commercial strain of Saccharomyces cerevisiae. Sensory analysis was carried out to assess the identification of experimental wine as Malvasia delle Lipari by defining its sensory profile. Fermentation with S. uvarum gave a final product with lower volatile acidity, lower alcohol content and higher total acidity. Moreover, differences in the aroma profile could be ascribed to different characteristics of the yeasts. Concerning sensorial analysis, the panel assigned higher scores in positive attributes to the wine fermented with S. uvarum